Comparative Analysis of Testing Approach in Context of Agile Software Development - Garima Nahar (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The Agile technique is becoming widely used by businesses worldwide to develop software products because it promises to provide high-quality products more quickly. Software testing is the most important way to evaluate a product's quality. Software testing in Agile development is still difficult and highly complex. This has mostly occurred as a result of Agile development's lack of emphasis on software testing activities. It emphasises frequent delivery, brief iterations, and client participation. This paper delves into a comparative analysis of testing approaches within the context of ASD. We explore traditional testing methodologies used in waterfall models and contrast them with techniques tailored for the iterative nature of agile projects. Key aspects like test automation, exploratory testing, and continuous integration will be discussed alongside their advantages and limitations in the agile environment. Finally, the paper concludes by outlining a potential framework for agile testing, integrating various techniques for optimal results.